Evaluations of clinical practice guidelines, protocols, and pathways used in rural and remote Australia, Canada, and Aotearoa New Zealand: a scoping review protocol ... - Hines, Sonia; Smith, James; Black, Oliver; Harvey, Gillian; Brand, Anthea; Arkapaw, Luke; Byrne, Mary (OSF Registries, 2024)
Review objective: The objective of this review protocol is to scope the extent and type of evidence describing evaluations of clinical practice guidelines, protocols, and pathways that are utilized in the rural and remote areas of Australia, Canada, and Aotearoa New Zealand. Review questions: The review will seek to answer the question: How are clinical practice guidelines, protocols, and pathways used in the rural and remote areas of Australia, Canada, and Aotearoa NZ being developed, implemented, and evaluated? Additionally, the review will address the following sub-questions: Are the clinical guidance resources (CGRs) being newly developed, adopted or adapted (contextualized) from other contexts and quality tested? What strategies are employed to implement the CGRs, and how are they selected and applied? What approaches and theories are being used to underpin the evaluations? Inclusion Criteria: Studies will be included from three high-income countries which have rural or remote regions and First Nations ...